Dynamic regulation of histone modifications and long-range chromosomal interactions during postmitotic transcriptional reactivation - Kang, Hyeseon; Shokhirev, Maxim N.; Xu, Zhichao; Chandran, Sahaana; Dixon, Jesse R.; HETZER, Martin W (Genes & Development)
During mitosis, transcription of genomic DNA is dramatically reduced, before it is reactivated during nuclear reformation in anaphase/telophase. Many aspects of the underlying principles that mediate transcriptional memory and reactivation in the daughter cells remain unclear. Here, we used ChIP-seq on synchronized cells at different stages after mitosis to generate genome-wide maps of histone modifications. Combined with EU-RNA-seq and Hi-C analyses, we found that during prometaphase, promoters, enhancers, and insulators retain H3K4me3 and H3K4me1, while losing H3K27ac. Enhancers globally retaining mitotic H3K4me1 or locally retaining mitotic H3K27ac are associated with cell type-specific genes and their transcription factors for rapid transcriptional activation. As cells exit mitosis, promoters regain H3K27ac, which correlates with transcriptional reactivation. Insulators also gain H3K27ac and CCCTC-binding factor (CTCF) in anaphase/telophase. This increase of H3K27ac in anaphase/telophase is required for posttranscriptional activation and may play a role in the establishment of topologically associating domains (TADs). Together, our results suggest that the genome is reorganized in a sequential order, in which histone methylations occur first in prometaphase, histone acetylation, and CTCF in anaphase/telophase, transcription in cytokinesis, and long-range chromatin interactions in early G1. We thus provide insights into the histone modification landscape that allows faithful reestablishment of the transcriptional program and TADs during cell division.
Keywords: Developmental Biology; Genetics

Tpr regulates the total number of nuclear pore complexes per cell nucleus - McCloskey, Asako; Ibarra, Arkaitz; HETZER, Martin W (Genes & Development)
The total number of nuclear pore complexes (NPCs) per nucleus varies greatly between different cell types and is known to change during cell differentiation and cell transformation. However, the underlying mechanisms that control how many nuclear transport channels are assembled into a given nuclear envelope remain unclear. Here, we report that depletion of the NPC basket protein Tpr, but not Nup153, dramatically increases the total NPC number in various cell types. This negative regulation of Tpr occurs via a phosphorylation cascade of extracellular signal-regulated kinase (ERK), the central kinase of the mitogen-activated protein kinase (MAPK) pathway. Tpr serves as a scaffold for ERK to phosphorylate the nucleoporin (Nup) Nup153, which is critical for early stages of NPC biogenesis. Our results reveal a critical role of the Nup Tpr in coordinating signal transduction pathways during cell proliferation and the dynamic organization of the nucleus.
Keywords: Developmental Biology; Genetics

Nup98 recruits the Wdr82–Set1A/COMPASS complex to promoters to regulate H3K4 trimethylation in hematopoietic progenitor cells - Franks, Tobias M.; McCloskey, Asako; Shokhirev, Maxim Nikolaievich; Benner, Chris; Rathore, Annie; HETZER, Martin W (Genes & Development)
Recent studies have shown that a subset of nucleoporins (Nups) can detach from the nuclear pore complex and move into the nuclear interior to regulate transcription. One such dynamic Nup, called Nup98, has been implicated in gene activation in healthy cells and has been shown to drive leukemogenesis when mutated in patients with acute myeloid leukemia (AML). Here we show that in hematopoietic cells, Nup98 binds predominantly to transcription start sites to recruit the Wdr82–Set1A/COMPASS (complex of proteins associated with Set1) complex, which is required for deposition of the histone 3 Lys4 trimethyl (H3K4me3)-activating mark. Depletion of Nup98 or Wdr82 abolishes Set1A recruitment to chromatin and subsequently ablates H3K4me3 at adjacent promoters. Furthermore, expression of a Nup98 fusion protein implicated in aggressive AML causes mislocalization of H3K4me3 at abnormal regions and up-regulation of associated genes. Our findings establish a function of Nup98 in hematopoietic gene activation and provide mechanistic insight into which Nup98 leukemic fusion proteins promote AML.
Keywords: Developmental Biology; Genetics

Nucleoporin-mediated regulation of cell identity genes - Ibarra, Arkaitz; Benner, Chris; Tyagi, Swati; Cool, Jonah; HETZER, Martin W (Genes & Development)
The organization of the genome in the three-dimensional space of the nucleus is coupled with cell type-specific gene expression. However, how nuclear architecture influences transcription that governs cell identity remains unknown. Here, we show that nuclear pore complex (NPC) components Nup93 and Nup153 bind superenhancers (SE), regulatory structures that drive the expression of key genes that specify cell identity. We found that nucleoporin-associated SEs localize preferentially to the nuclear periphery, and absence of Nup153 and Nup93 results in dramatic transcriptional changes of SE-associated genes. Our results reveal a crucial role of NPC components in the regulation of cell type-specifying genes and highlight nuclear architecture as a regulatory layer of genome functions in cell fate.
Keywords: Developmental Biology; Genetics

Evolution of a transcriptional regulator from a transmembrane nucleoporin - Franks, Tobias M.; Benner, Chris; Narvaiza, Iñigo; Marchetto, Maria C.N.; Young, Janet M.; Malik, Harmit S.; Gage, Fred H.; HETZER, Martin W (Genes & Development)
Nuclear pore complexes (NPCs) emerged as nuclear transport channels in eukaryotic cells ∼1.5 billion years ago. While the primary role of NPCs is to regulate nucleo–cytoplasmic transport, recent research suggests that certain NPC proteins have additionally acquired the role of affecting gene expression at the nuclear periphery and in the nucleoplasm in metazoans. Here we identify a widely expressed variant of the transmembrane nucleoporin (Nup) Pom121 (named sPom121, for “soluble Pom121”) that arose by genomic rearrangement before the divergence of hominoids. sPom121 lacks the nuclear membrane-anchoring domain and thus does not localize to the NPC. Instead, sPom121 colocalizes and interacts with nucleoplasmic Nup98, a previously identified transcriptional regulator, at gene promoters to control transcription of its target genes in human cells. Interestingly, sPom121 transcripts appear independently in several mammalian species, suggesting convergent innovation of Nup-mediated transcription regulation during mammalian evolution. Our findings implicate alternate transcription initiation as a mechanism to increase the functional diversity of NPC components.
Keywords: Developmental Biology; Genetics

Nuclear pore proteins and the control of genome functions - Ibarra, Arkaitz; HETZER, Martin W (Genes & Development)
Nuclear pore complexes (NPCs) are composed of several copies of ∼30 different proteins called nucleoporins (Nups). NPCs penetrate the nuclear envelope (NE) and regulate the nucleocytoplasmic trafficking of macromolecules. Beyond this vital role, NPC components influence genome functions in a transport-independent manner. Nups play an evolutionarily conserved role in gene expression regulation that, in metazoans, extends into the nuclear interior. Additionally, in proliferative cells, Nups play a crucial role in genome integrity maintenance and mitotic progression. Here we discuss genome-related functions of Nups and their impact on essential DNA metabolism processes such as transcription, chromosome duplication, and segregation.
Keywords: Developmental Biology; Genetics

The nucleoporin Nup153 regulates embryonic stem cell pluripotency through gene silencing - Jacinto, Filipe V.; Benner, Chris; HETZER, Martin W (Genes & Development)
Nucleoporins (Nups) are a family of proteins best known as the constituent building blocks of nuclear pore complexes (NPCs), membrane-embedded channels that mediate nuclear transport across the nuclear envelope. Recent evidence suggests that several Nups have additional roles in controlling the activation and silencing of developmental genes; however, the mechanistic details of these functions remain poorly understood. Here, we show that depletion of Nup153 in mouse embryonic stem cells (mESCs) causes the derepression of developmental genes and induction of early differentiation. This loss of stem cell identity is not associated with defects in the nuclear import of key pluripotency factors. Rather, Nup153 binds around the transcriptional start site (TSS) of developmental genes and mediates the recruitment of the polycomb-repressive complex 1 (PRC1) to a subset of its target loci. Our results demonstrate a chromatin-associated role of Nup153 in maintaining stem cell pluripotency by functioning in mammalian epigenetic gene silencing.
Keywords: Developmental Biology; Genetics

Evolution and function of genomic imprinting in plants - Rodrigues, Jessica A.; Zilberman, Daniel (Genes and Development)
Genomic imprinting, an inherently epigenetic phenomenon defined by parent of origin-dependent gene expression, is observed in mammals and flowering plants. Genome-scale surveys of imprinted expression and the underlying differential epigenetic marks have led to the discovery of hundreds of imprinted plant genes and confirmed DNA and histone methylation as key regulators of plant imprinting. However, the biological roles of the vast majority of imprinted plant genes are unknown, and the evolutionary forces shaping plant imprinting remain rather opaque. Here, we review the mechanisms of plant genomic imprinting and discuss theories of imprinting evolution and biological significance in light of recent findings.

The Arabidopsis BODENLOS gene encodes an auxin response protein inhibiting MONOPTEROS-mediated embryo patterning - Hamann, Thorsten; Benková, Eva; Bäurle, Isabel; Kientz, Marika; Jürgens, Gerd (Genes and Development)
Developmental responses to the plant hormone auxin are thought to be mediated by interacting pairs from two protein families: short-lived inhibitory IAA proteins and ARF transcription factors binding to auxin-response elements. Monopteros mutants lacking activating ARF5 and the auxin-insensitive mutant bodenlos fail to initiate the root meristem during early embryogenesis. Here we show that the bodenlos phenotype results from an amino-acid exchange in the conserved degradation domain of IAA12. BODENLOS and MONOPTEROS interact in the yeast two-hybrid assay and the two genes are coexpressed in early embryogenesis, suggesting that BODENLOS inhibits MONOPTEROS action in root meristem initiation.

BIG: A calossin-like protein required for polar auxin transport in Arabidopsis - Gil, Pedro; Dewey, Elizabeth; Friml, Jirí; Zhao, Yunde; Snowden, Kimberley; Putterill, Jo; Palme, Klaus; Estelle, Mark; Chory, Joanne (Genes and Development)
Polar auxin transport is crucial for the regulation of auxin action and required for some light-regulated responses during plant development. We have found that two mutants of Arabidopsis - doc1, which displays altered expression of light-regulated genes, and tir3, known for its reduced auxin transport - have similar defects and define mutations in a single gene that we have renamed BIG. BIG is very similar to the Drosophila gene Calossin/Pushover, a member of a gene family also present in Caenorhabditis elegans and human genomes. The protein encoded by BIG is extraordinary in size, 560 kD, and contains several putative Zn-finger domains. Expression-profiling experiments indicate that altered expression of multiple light-regulated genes in doc1 mutants can be suppressed by elevated levels of auxin caused by overexpression of an auxin biosynthetic gene, suggesting that normal auxin distribution is required to maintain low-level expression of these genes in the dark. Double mutants of tir3 with the auxin mutants pin1, pid, and axr1 display severe defects in auxin-dependent growth of the inflorescence. Chemical inhibitors of auxin transport change the intracellular localization of the auxin efflux carrier PIN1 in doc1/tir3 mutants, supporting the idea that BIG is required for normal auxin efflux.

A mutation in the Gsk3-binding domain of zebrafish Masterblind/Axin1 leads to a fate transformation of telencephalon and eyes to diencephalon - Heisenberg, Carl-Philipp J; Houart, Corinne; Take Uchi, Masaya; Rauch, Gerd; Young, Neville; Coutinho, Pedro; Masai, Ichiro; Caneparo, Luca; Concha, Miguel; Geisler, Robert; Dale, Trevor; Wilson, Stephen; et al. (Genes and Development)
Zebrafish embryos homozygous for the masterblind (mb1) mutation exhibit a striking phenotype in which the eyes and telencephalon are reduced or absent and diencephalic fates expand to the front of the brain. Here we show that mb1(-/-) embryos carry an amino-acid change at a conserved site in the Wnt pathway scaffolding protein, Axin1. The amino-acid substitution present in the mbl allele abolishes the binding of Axin to Gsk3 and affects Tcf-dependent transcription. Therefore, Gsk3 activity may be decreased in mbl(-/-) embryos and in support of this possibility, overexpression of either wild-type Axin1 or Gsk3 beta can restore eye and telencephalic fates to mb1(-/-) embryos. Our data reveal a crucial role for Axin1-dependent inhibition of the Wnt pathway in the early regional subdivision of the anterior neural plate into telencephalic, diencephalic, and eye-forming territories.

Two mammalian helix-loop-helix factors structurally related to Drosophila hairy and Enhancer of split - Sasai, Yoshiki; Kageyama, Ryoichiro; Tagawa, Yoshiaki; Shigemoto, Ryuichi; Nakanishi, Shigetada (Genes and Development)
We report the molecular characterization of two novel rat helix-loop-helix (HLH) proteins, designated HES-1 and HES-3, that show structural homology to the Drosophila hairy and Enhancer of split [E(spl)] proteins, both of which are required for normal neurogenesis. HES-1 mRNA, expressed in various tissues of both embryos and adults, is present at a high level in the epithelial cells, including the embryonal neuroepithelial cells, as well as in the mesoderm-derived tissues such as the embryonal muscle. In contrast, HES-3 mRNA is produced exclusively in cerebellar Purkinje cells. HES-1 represses transcription by binding to the N box, which is a recognition sequence of E(spl) proteins. Interestingly, neither HES-1 nor HES-3 alone interacts efficiently with the E box, but each protein decreases the transcription induced by E-box-binding HLH activators such as E47. Furthermore, HES-1 also inhibits the functions of MyoD and MASH1 and effectively diminishes the myogenic conversion of C3H10T1/2 cells induced by MyoD. These results suggest that HES-1 may play an important role in mammalian development by negatively acting on the two different sequences while HES-3 acts as a repressor in a specific type of neurons.